Children who are exposed to intimate partner violence: Interviewing mothers to understand its impact on children. (October 2015) - Izaguirre, Ainhoa; Calvete, Esther
Abstract: Children's victimization related to intimate partner violence (IPV) has damaging effects on their well-being and development. The purpose of this research was to assess the impact of IPV on children's emotional and behavioral problems through their mothers' narratives. A total of 30 Spanish mothers (mean age = 41.57 years, SD  = 8.54 years) were individually interviewed. The results showed that many of the children directly suffered from aggression, and most of them witnessed IPV. As a result of their exposure to violence, children often develop psychological, social, and school problems. Their learning of aggressive behaviors is especially remarkable, and these behaviors are sometimes directed towards their mothers. Thus, women can suffer a twofold victimization: by their partner and by their children. These additional problems contribute to hindering the recovery process of victims. Fortunately, not all children develop problems as a result of exposure to IPV; some of them are capable of mature responses.